EXPERIMENTAL STUDIES ON THE MECHANICAL BEHAVIOUR OF TWO THERMAL CRACKED MARBLES - Ferrero A.M.; Marini P. (My University, 2001)
The speci®c aim of this paper is to ®nd an experimental methodology which could measure crack density in rock and its in¯uence on the behaviour of the rock material. The results of both experimental and numerical simulations showed that rock behaviour is mainly ruled by crack density within a speci®c rock volume. The behaviour of a rock with di¨erent crack densities has been studied by several authors, from the theoretical point of view and through experiments.